Vibração: soldados sempre em forma, soldados fieis - Feijó, Olavo Guimarães (Revista de Educação Física / Journal of Physical Education, 2017)
Introdução: Motivação é a mola que energiza e orienta nosso comportamento, na direção dos alvos subjetivos, que todo ser jumano desenvolve; pode ter caráter interno ou externo. Objetivo: Comentar sobre a motivação no contexto da preparação profissional de militares. Conclusão: Mais do que motivação externa, o desenvolvimento de motivação interna, junto com o condicionamento físico, é de alto interesse para a preparação dos profissionais militares. Vibration: Soldiers always in Good Shape, Faithful Soldiers Abstract Introduction: Motivation is the spring that energizes and guides our behavior toward the subjective targets that every Juman being develops; May have internal or external character. Objective: Analyze the motivation in the context of the physical and professional preparation of military personnel.Introduction: Motivation is the spring that energizes and guides our behavior toward the subjective targets that every Juman being develops; May have internal or external character. Conclusion: More than external motivation, together with the physical conditioning training, the development of internal motivation is of great interest for military professionals’ preparation.